Behavioural and Policy Drivers of Electric Vehicle Repurchase Intention in Malaysia: Insights for an Inclusive Energy Transition - Chong, Kim Mee; Aziz, Atif; Parveen, Manam; He, Long; Pardaev, Jamshid (International Journal of Energy Economics and Policy, 2025)
As Malaysia advances toward a low-carbon transportation future, understanding electric vehicle (EV) repurchase intention is critical for sustainable market growth. This study investigates behavioural and policy-related determinants of EV repurchase intention among 500 Malaysian respondents with direct household EV ownership experience. Utilising the Theory of Planned Behaviour (TPB), the New Ecological Paradigm (NEP) and findings from technology acceptance research, we investigate the influence of environmental attitudes, personal norms, perceived behavioural control, governmental incentives, infrastructure preparedness and trust in technology on outcomes, with driving experience serving as a connecting factor. The resulting SEM analysis indicates that environmental attitudes, personal norms and perceived behavioural control are the primary factors influencing individuals to repurchase electric vehicles. Government incentives and infrastructure readiness indirectly affect repurchase decisions by influencing the entire driving experience. Conversely, subjective norms exert a minimal influence. While trust in technology improves the driving experience, it doesn’t significantly affect the purchasing decision of another EV. The findings underline the significance of consumer’s personal motivation and a sense of empowerment in sustaining long-term electric vehicle commitment. It advises that Malaysian policy should focus on techniques to cultivate loyalty and sustained support rather than solely offering incentives for the initial purchase. This strategy can foster a practical and sustainable energy transition while enhancing Malaysia’s electric vehicle ecosystem.